2019
DOI: 10.1515/cdbme-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lung volume changes on perfusion estimates derived by Electrical Impedance Tomography

Abstract: Electrical Impedance Tomography (EIT), an imaging technique which operates non-invasively and without radiation exposure, provides information about ventilation- and cardiac-synchronous (pulsatile) changes in the lung. It is well known, that perfusion within the thorax is influenced by lung volume or intrathoracic pressure. In this observational study, it shall be investigated if this phenomenon can be monitored by EIT. Therefore, the impact of the amount of air within the lung on the pulsatile EIT signal was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, each EIT signal section was separated into smaller signal segments corresponding to one heart beat ( Figure 2). A linear trend between the start and end point of each signal segment was removed as well as an interpolation of each signal segment to the mean length of all signal segments was conducted (refer to [4]). Subsequently, for each 2 to 3 minutes section, the mean signal of all signal segments was calculated ( Figure 2).…”
Section: Eit and Blood Gas Analysis 231 Eit Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, each EIT signal section was separated into smaller signal segments corresponding to one heart beat ( Figure 2). A linear trend between the start and end point of each signal segment was removed as well as an interpolation of each signal segment to the mean length of all signal segments was conducted (refer to [4]). Subsequently, for each 2 to 3 minutes section, the mean signal of all signal segments was calculated ( Figure 2).…”
Section: Eit and Blood Gas Analysis 231 Eit Data Analysismentioning
confidence: 99%
“…In a previous study, we assessed changes in the pulsatile impedance signal depending on lung volume during breath holding (approx. 10 seconds) in a spontaneously breathing subject [4]. It was indicated that shape and amplitude of the pulsatile impedance signal varied based on changes in lung volume.…”
Section: Introductionmentioning
confidence: 99%